Effects of inverse ratio ventilation combined with lung protective ventilation on pulmonary function in patients with severe burns for surgery. Issue 1 (1st January 2020) - Yang, Yan-Chao; Huai, Qiao; Cui, Shu-Zhen; Cao, Xiao-Wei; Gao, Bu-Lang
ABSTRACT: Objective: To investigate the effects of inverse ratio ventilation combined with lung-protective ventilation on pulmonary function and inflammatory factors in severe burn patients undergoing surgery. Populations and Methods : Eighty patients with severe burns undergoing elective surgery were divided randomly into two groups: control (CG, n = 40) and experiment (EG, n = 40). The CG had conventional ventilation, whereas the EG were ventilated with tidal volume (TV) of 6–8 ml/kg, I (inspiration): E (expiration) of 2:1, and positive end-expiratory pressure (PEEP) 5 cm H2O. The following variables were evaluated before (T0), 1 h after start of surgery (T1) and after surgery (T2): oxygenation index (OI), partial pressure of carbon dioxide (PaCO2 ), TV, peak airway pressure (Ppeak), mean airway pressure (Pmean), PEEP, pulmonary dynamic compliance (Cdyn), alveolar–arterial difference of oxygen partial pressure D(A-a)O2, lactic acid (Lac), interleukin (IL)-6 and IL-10, and lung complications. Results : At T1 and T2 time points, the OI, Pmean and Cdyn were significantly greater in the EG than in the CG while the TV, Ppeak, D(A-a)O2, IL-6 and IL-10 were significantly smaller in the EG than in the CG. At the end of the surgery, the Lac was significantly smaller in the EG than in the CG (1.28 ± 0.19 vs. 1.40 ± 0.23 mmol/L). Twenty-four hours after the surgery, significantly more patients had hypoxemia (27.5 vs. 10.0%), increased expectoration (45.0 vs. 22.5%), increased lung texture or exudation (37.5 vs. 17.5%) in the CG than in the EG. Conclusions : Inverse ratio ventilation combined with lung-protective ventilation can reduce Ppeak, increase Pmean and Cdyn, improve the pulmonary oxygenation function, and decrease ILs in severe burn surgery patients.